Citizenship ‘from Above’? The Case of Chile, 1964-2010 - van der Ree, Gerard (European Review of Latin American and Caribbean Studies, 2011)
During the last fifty years, citizenship in Chile has been re-interpreted and reformulated in different ways. By combining top-down and bottom-up approaches towards citizenship, this article argues that the reformulation of citizenship in Chile has been brought about through both state-initiated projects and civil society responses, which have interacted over time. State projects have been based on ideological doctrines in order to resolve problems emanating from ‘below’, while civil society responses have come from the ways in which the state have sought to implement its projects. Even though this historical process has produced both periods of rapid expansion and radical restriction of citizenship, in the end it produced a stable but asymmetric model of citizenship in Chile.Resumen: ¿Ciudadanía ‘desde arriba’? El caso de Chile, 1964-2010Durante los últimos cincuenta años, la ciudadanía en Chile ha sido re-interpretada y reformulada de diferentes modos. Combinando las aproximaciones descendentes y ascendentes, en este artículo se defiende que la reformulación de la ciudadanía en Chile fue provocada tanto por proyectos iniciados por el estado como por respuestas de la sociedad civil, que, con el tiempo, han llegado a interactuar. Los proyectos estatales se han basado en doctrinas ideológicas para resolver problemas que emanaban desde ‘abajo’, mientras que las respuestas de la sociedad civil han sido provocadas por las maneras en que el estado ha intentado implementar sus proyectos. Aunque el proceso histórico ha producido tanto periodos de rápida extensión como de radicales restricciones de la ciudadanía, al final resultó en Chile un modelo estable, aunque asimétrico.